The Effect of Affiliate Programs and Consumer Behavior on Profit Margins: The Mediating Role of Customer Acquisition Cost (CAC) and Customer Loyalty - Muchlis Abbas; Ibrahim Ibrahim; Rusdiah Hasanuddin; Fitri Fitri; Rahmawati Umar (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The purpose of this study is to investigate the influence of affiliate programs on profit margins in online businesses, with a focus on understanding the mediating role of Customer Acquisition Cost (CAC) and Customer Loyalty. The study aims to bridge the knowledge gap and provide insights for business practitioners and researchers to design more effective affiliate program strategies. This research adopts a comprehensive approach, reviewing current literature on affiliate programs and online businesses. The study focuses on the mediating role of Customer Acquisition Cost (CAC) and Customer Loyalty in the relationship between affiliate programs and profit margins. The research methodology includes data analysis and interpretation to unravel the impact of affiliate programs on CAC, customer loyalty, and profit margins with 200 respondents as participant and use SMART-PLS 3.0 as statistical tools. The findings of this research reveal that implementing affiliate programs can result in higher acquisition costs due to commissions paid to affiliate partners. However, effective affiliate programs can create customer attachment, leading to increased customer retention and maximizing customer lifetime value. Affiliate programs contribute to overall business profitability by increasing sales volume, broadening the customer base, and generating additional revenue. Moreover, the study highlights the significant positive effect of consumer behavior on customer acquisition cost. However, the influence of customer acquisition cost on profit margins is not significant, contrary to traditional business theory. This research makes an important contribution to the understanding of the influence of affiliate programs in online businesses and the mediating role of CAC and Customer Loyalty in driving profit margins. The study offers valuable insights for business practitioners and researchers to design more effective affiliate program strategies and maximize profit margins in the competitive e-commerce environment. Further research is needed to explore the relationship between customer acquisition cost and profit margins in more depth and identify other related factors.